Jewish Terrorism and the Modern Middle East - Charters, David A. (Journal of Conflict Studies, 2007)
This article begins with a question: can the contemporary Middle East conflict itself, in which terrorism plays a prominent role, be traced to a successful terrorist campaign? I argue that Jewish terrorism in 1940s Palestine was both tactically and strategically significant. At the tactical level, Jewish terrorists were able to erode the ability of British security forces to control Palestine. Strategically, that persuaded Britain to withdraw from Palestine, which, in turn, created the conditions that facilitated both the founding of Israel and the creation of an Arab-Palestinian diaspora. The consequent Arab-Israeli conflict has shaped and dominated Middle East politics and diplomacy for much of the last 60 years. Thus, Jewish terrorism left the region with a dual legacy of tactical effectiveness and strategic influence. This article explores and assesses this dual legacy.